Analysis of the Implementation of Good Public Governance at the Ministry of Industry - Mikris Nalle; M. L. Denny Tewu (Budapest International Research and Critics University, 2022)
Analysis of the implementation of good public governance at the Ministry of Industry. This research is about the actual implementation of good governance, especially at the Ministry of Industry Office. Based on research that has been conducted, the Office of the Ministry of Industry has not implemented or implemented the values of good governance in a committed manner, especially with regard to professionalism, transparency, accountability and excellent service. The research method used is a qualitative research method where one of the research procedures produces descriptive data and the data obtained are more complete, more in-depth so that the research objectives can be achieved. The research location is at the Ministry of Industry. The author collects research data from several books, government regulations, journals and in-depth interviews with research informants, namely employees of the Ministry of Industry. This study concludes that the obstacles in the implementation of good governance at the Ministry of Industry are in accordance with applicable laws and regulations. So that there are no obstacles in carrying out a policy especially those related to the community.